Review of CAD-model capabilities and restrictions for multidisciplinary use. Issue 4 (4th July 2018) - Heikkinen, Tim; Johansson, Joel; Elgh, Fredrik
ABSTRACT: Product development is an iterative process, partially due to changes in both company internal and external product requirements, resulting in changes to the product under development. These changes might require recapitulation of design rationale and result in re-doing assessments and syntheses of different kinds. One way to support this work is to proactively model in such a way that as much as possible of the previous work can be re-used. Not only within one product development project but also across and to future ones. Modelling for re-use can be done by documenting design rationale and formalising performed activities as design guidelines or computer scripts. To be able to find and re-use this information it could be attached to the product features which it relates to. Since geometry is such a core product characteristic, especially within the mechanical industry, and is often modelled as CAD-models, this paper presents a review of CAD-model capabilities and restrictions to serve as a carrier of multidisciplinary information. This is done by; enquiring three Swedish companies, exploring an automated Finite Element Analysis method utilising the CAD-model as a carrier of information, and reviewing different CAD software capabilities. Results show that there are at least seven extension techniques, out of which all are currently being used or considered to be in the future, by at least one company. Further, depending on the extension technique, extendibility and human-comprehension of the added information differ. GRAPHICAL ABSTRACT: